Anatomy of a Textile Cluster – Problems and Prospects of Textile Business Owner with Respect to Business Expansion and Operations - Nalini Palaniswamy; Muruganandam Duraiswamy (International Journal of Engineering and Management Research, 2018)
The study on Anatomy of a textile cluster - problems and prospects of textile business owners with respect to business expansion and operations was carried out to find the problems and prospects of Erode textile cluster as a pilot survey with a sample size of 80 respondents. The primary study was carried out in two stages. An exploratory study was done among the textile merchants and textile buyers to understand the nature, administration, status, problems and scope of the textile merchants in Erode Cluster. Firstly, the researcher had personnel interview with the officials of four major textile markets namely, Texvalley, Gani market, Ashokapuram market, and central market.Secondly an interview schedule was carried with a structured questionnaire . The interview schedule was prepared with four variables namely business factors, financial factors, marketing factors and market facility concerned. Each items in the variable was measured with a 5 point Likert scale. And there were few items which captured their present level operations and future plans. The results revealed the present status of their operations which is a key in factors for planning for a better operational efficiency for next level.